Does Microfinance Outreach Indonesian Micro and Small Enterprises? - Martokoesoemo, Dewi Ratna Sjari; Sihombing, Ariel Bhaskara Haposan (School of Business, IPB University (SB-IPB), 2025)
Background: Micro and Small Enterprises (MSEs) played role in Indonesia’s economy. However, Indonesian MSEs still faced various challenges in obtaining external financing. Microfinance had emerged as a prominent tool for reducing the credit constraints experienced by MSEs. However, the literature on the effectiveness of microfinance in improving MSE performance still had empirical gaps in terms of mixed results.Purpose: This study examines the impact of microfinance on the asset growth of micro and small enterprises (MSEs) in Indonesia using data from the fifth wave of the Indonesia Family Life Survey (IFLS).Design/methodology/approach: The analysis encompassed a cross-sectional dataset of 6,363 MSEs across 16 business categories and employs Ordinary Least Squares regression to measure the effects of exogenous variations in microfinance access on total assets.Finding/Result: Regression analyses reveal that microfinance significantly increases MSEs’ total assets by 19%-25%, with smaller firms showing stronger effects. Alternative measures of microfinance, such as awareness of institutions and loan values, also demonstrate a positive impact on firm outcomes, whereas financing from informal institutions is associated with negative effects. Additional findings highlight the positive influence of microfinance on non-equipment assets, revenue, and expenses, although its effect on equipment assets is weaker. Robustness checks across subsamples confirm the results, indicating diminishing returns for larger firms than smaller firms.Conclusions: These findings underscore the critical role of microfinance in enhancing the growth and sustainability of MSEs, particularly smaller, vulnerable enterprises. This study emphasizes the need for tailored microfinance interventions and suggests further exploration of long-term impacts and integrated support mechanisms. This study provides valuable insights for policymakers to optimize microfinance programs, contributing to poverty alleviation and economic empowerment in Indonesia.Originality/value: The existing literature has not sufficiently examined how microfinance can alleviate these financial pressures and enhance MSE resilience and performance. This study aims to address this gap by evaluating the impact of microfinance on the performance of MSEs in Indonesia, providing a comprehensive understanding of how improved access to microfinance can support MSEs in overcoming financial barriers and sustaining growth despite experiencing adverse shocks. Keywords: microfinance, micro and small enterprise, asset growth, Indonesian family life survey